Gender Construction in Feminist Da'wah by Women Preachers on Youtube - Muhammad Taufiq Syam; Abdullah Thahir; Nurhikmah Nurhikmah; Mifda Hilmiyah (Jurnal Dakwah Risalah, 2021)
Feminist da'wah by women preachers on YouTube has formed Muslim interaction relationships that play a role in helping spread the teachings of Islam, especially for Muslim women who are packaged in da'wah messages that construct the role of women in the domestic sphere. This study uses a qualitative method with a case study approach and qualitative descriptive to describe various conditions, situations or phenomena of social reality that occur on social media. Data collection techniques were carried out by documentation, observation and focus group discussion. Based on the results of data analysis, it was found that the construction of gender identity through the externalization process of adjustment to social reality, objectivation by using Islamic normative legal basis and internalization through acceptance and determination of choices in action. The cognitive reduction that occurs gives birth to the assumption of dominance, the assumption of limitation and the assumption of deviation in representing a da'wah message. Adjustments to the principle of justice and the basic conditions experienced by a woman are needed in understanding the message of da'wah.